Digital Marketing Shopee, Media Pomosi Dan Kualitas Produk Terhadap Peningkatan Omset Penjualan (Studi kasus pada penjualan Bykris Beauty) - Amalia Rohmatul Kamalia; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis research was conducted by Bykris Beauty in Bahudan Hamlet RT.04 RW. 02 Wuluh Village, Kesamben District, Jombang Regency. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of digital marketing, promotional media and product quality on sales turnover. The independent variables used are digital marketing, promotional media and product quality, while the dependent variable is sales turnover. The sample used in this study were 89 respondents who were consumers of Bykris Beauty. Data collection techniques using a questionnaire. The analytical method used is the instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using SPSS 16.0 computer software for data processing. The results of this study indicate that digital marketing affects sales turnover, promotional media affects sales turnover and product quality affects sales volume. Digital marketing, promotional media and product quality simultaneously affect sales turnover. Keywords : Digital Marketing, Promotional Media, Product Quality And Sales Turnover.